Analisis Peningkatan Service Level Warehouse Melalui Pengukuran Kepuasan Pelanggan Dengan Metode Servqual Studi Kasus PT XYZ - Siahaan, Yessica Bunga Uli; Poncotoyo, Wahyu; Pratiwi, Sekar Widyastuti (Institut Transportasi dan Logistik Trisakti, 2023)
Service quality is one of the main benchmarks in the retail industry. High-quality service makes a retail business more competitive and enhances the company’s image. Excellent warehouse service is also a key aspect of evaluating warehouse service levels. The retail company under study in this research is PT XYZ, one of the top three retail companies in Indonesia. Data from the past six months, from January to June 2024, shows a significant decline in service levels in February, dropping to 74%. This indicates that the company failed to meet its monthly service level target of 75% in February. In this study, service quality is the main focus, measured using the Service Quality (SERVQUAL) method, which covers five dimensions: Tangibles, Reliability, Responsiveness, Assurance, and Empathy. The initial stage of this research involved analyzing the shortcomings in PT XYZ, particularly in the warehouse service quality. After identifying and analyzing the issues, a questionnaire was distributed to customers to understand the root causes of the problem. The results showed that, among the SERVQUAL dimensions, Reliability had the lowest quality score, while Tangibles had the highest.